Board Gender Diversity Dan Board Education Diversity terhadap Bank-Risk Taking - Fani Khoirotunnisa (UMSurabaya Publishing, 2021)
The benefit of gender and education diversity on the board of commissioners is a subject of the current debate. This research investigates board gender diversity and board education diversity on bank risk-taking in Indonesian listed banks. Using a sample of 40 Indonesian banks over a period from 2012 to 2018, we find that board gender diversity has a significant negative effect on bank risk-taking. In contrast, the nationality diversity between bank's board members does not directly impact bank risk-taking. This study concludes that the more significant the proportion of women on the bank's board, the less risk the bank has. Keywords : Board Gender Diversity; Board Education Diversity; Bank Risk-TakingCorrespondence to : fani.khoiro.mnj@upnjatim.ac.id Manfaat keberagaman jenis kelamin dan latar belakang pendidikan dewan komisaris menjadi topik perdebatan akhir-akhir ini. Penelitian ini mengkaji dampak dari keberagaman jenis kelamin dan latar belakang pendidikan dewan komisaris terhadap pengambilan risiko bank di bank-bank yang terdaftar di Indonesia. Dengan menggunakan sampel dari 40 bank di Indonesia selama periode dari 2012 hingga 2018, peneliti menemukan bahwa keragaman jenis kelamin dewan memiliki pengaruh negatif yang signifikan terhadap pengambilan risiko bank. Sebaliknya, perbedaan latar belakang pendidikan tidak berdampak langsung pada pengambilan risiko bank. Kesimpulan dari penelitian ini adalah semakin besar proporsi wanita dalam dewan komisaris bank maka semakin kecil tingkat pengambilan risiko bank. Kata Kunci : Board Gender Diversity; Board Education Diversity; Bank Risk-Taking